EVOLUTION OF THE CONCEPT “COLD WAR” IN ENGLISH POLITICAL DISCOURSE - Allabergenova Munira (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The concept of the “Cold War” has traditionally referred to the geopolitical tension between the United States and the Soviet Union in the second half of the twentieth century. However, in modern English political discourse, especially in mass media, this concept has undergone significant transformation. This article examines how the term “Cold War” is used in contemporary media texts and how its meaning has expanded beyond its original historical context. The study finds that the term is frequently used metaphorically to describe new forms of political, economic, technological, and ideological rivalry. The analysis shows that mass media plays a key role in shaping and spreading these new interpretations. The research concludes that the concept of “Cold War” has evolved into a flexible discursive tool in modern political communication.